Communication Strategies on the TikTok Account OH! SOME in Building Audience Interaction - Muhammad Yanuar Ashiddiqie; Hani Astuti; Sigit Surahman; Prasojo Prasojo (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
The fast-paced growth of digital technology and online communication has transformed how people connect, share information, and build communities. Among the many social media platforms, TikTok stands out for its ability to create dynamic and interactive engagement through short-form videos and live streaming features. This study explores how the retail brand OH! SOME uses communication strategies on TikTok to foster meaningful interaction with its audience. Drawing on Chriss Fill’s (1995) three-stage communication framework—Pull, Push, and Profile Strategies—the research examines how these approaches are implemented across OH! SOME’s beauty, makeup, and skincare accounts. A qualitative descriptive method was employed, combining in-depth interviews, direct observation, and documentation with three key participant roles: the operator, live streaming assistants, and hosts. The findings reveal that OH! SOME’s communication success on TikTok relies on its ability to integrate creative content with real-time interaction. The Pull Strategy attracts audiences through engaging visuals and relatable messages; the Push Strategy emphasizes teamwork and consistent interaction during live sessions; and the Profile Strategy strengthens brand image and trust among followers. Overall, the study highlights how classical communication theories can be adapted to the dynamics of digital marketing. It provides both conceptual and practical insights for brands seeking to build audience relationships in the era of social commerce. The results also underline TikTok’s potential not merely as a sales tool but as a space for creating community, authenticity, and emotional connection with consumers.